Biomass-Fueled Organic Rankine Cycles: State of the Art and Future Trends - Heidarnejad, Parisa; Genceli, Hadi; Hashemian, Nasim; Asker, Mustafa; Al-Rawi, Mohammad (MDPI, 2024)
Biomass-fueled organic Rankine cycles (ORCs) are widely utilized technologies for power production because of their simplicity, low cost, and relatively high efficiencies. Furthermore, raw material availability and topographical independency make these systems preferable to other renewable-fueled power generation systems. A deep and comprehensive understanding of biomass-fueled organic Rankine cycles will provide researchers with a solid foundation to prioritize their investigations and assist future developments in this field. In this regard, feedstocks and their properties, biomass conversion mechanisms, and biomass-fueled power generation systems are discussed in this study. Power generation technologies based on coal and waste as feedstock have been widely investigated in the literature due to higher energy content and technological maturity. Additionally, depending on the type of biomass available, the scale of the power plant, and economic and environmental considerations, the most common technologies utilized for biomass conversion are combustion, gasification, and anaerobic digestion. Finally, the authors investigate various aspects of biomass-fueled organic Rankine cycles, including working fluids, analysis methods, and environmental issues. Since maximizing product yield is key in biomass-based power generation systems, technical assessment of these systems has been a primary focus of many studies. Further research is required on integrated environmental and socio-economic approaches, along with Machine Learning algorithms. Future advancements focusing on integration of feedstock with other renewable energy sources, efficient working fluids like nanofluids, and high-tech heat exchangers will drive the development of biomass-fueled ORC systems.
Keywords: biomass energy; environmental sustainability; multigeneration systems; organic Rankine cycle (ORC); WASTE HEAT-RECOVERY; LOW-GWP REFRIGERANTS; SMALL-SCALE APPLICATIONS; DROP-IN REPLACEMENT; BIO-OIL PRODUCTION; FIRED ORC SYSTEMS; MICRO-GAS-TURBINE; POWER-GENERATION; WORKING FLUIDS; BIOETHANOL PRODUCTION; Energy & Fuels